Left ventricular noncompaction and EcoScore: prognostic value of a new echographic risk score. (14th October 2021) - Correia, J; Neto, V; Ferreira, G; Pires, I; Santos, J; Goncalves, L; Cabral, J; Costa, A
Abstract: Introduction: Left Ventricular Non-Compaction (LVNC) is a rare and underdiagnosed cardiomyopathy, characterized by hypertrabeculation of the left ventricle. This disease is associated with high rates of morbidity and mortality; however, its main adverse prognostic factors are not well established. Aim: To create a risk score for LVNC based on echocardiographic criteria (EcoScore) to predict the occurrence of adverse events. Methods: The authors included patients with the diagnosis of LVNC, according to the Jenni Criteria. Clinical and echocardiographic data were evaluated and the occurrence of the following adverse events was reported: hospitalizations due to supraventricular or ventricular tachyarrythmias and heart failure, acute myocardial infarction, stroke, heart transplant and death. The follow-up time was 24 months. ROC curves to predict the occurrence of at least one adverse event were constructed for each echocardiographic parameter. The optimal cut-off obtained from each ROC curve was then used to attribute points (1 point per parameter). The EcoScore resulted from the sum of the obtained points. The authors finally created a ROC curve to predict the occurrence of any adverse event for the EcoScore. The statistical analysis was performed in SPSS. p value <0.05 was considered statistically significant. Results: 33 patients (48.5% male, age at diagnosis 45.9±21 years) were included in this study. The optimal cut-offs for each parameter obtained from the ROC curves were the following: left ventricle dyastolic diameter >55mm, left atrial diameter >40mm, pulmonary artery systolic pressure >22mmHg and left ventricle ejection fraction <40%. The area under the curve for the EcoScore to predict any adverse event was 0.850 (p=0.017) and an EcoScore >1 had a sensibility of 85.7% and a specificity of 70%. Conclusion: The EcoScore accurately predicted the occurrence of at least one adverse event in this population. Thus, it could be a good tool in the daily practice to select patients who may benefit from a more aggressive surveillance and treatment. Funding Acknowledgement: Type of funding sources: None.